تأثير الرش الورقي ببعض المركبات الدبالية والأحماض الأمينية في نمو وإنتاج الخيار في البيوت البلاستيكية - سليمان, نصر; غرة, ديما (Latakia University Journal -Biological Sciences Series, 2016)
أُجري البحث في بيت بلاستيكي غير مدفأ للموسم الزراعي 2014-2013، في قرية القنجرة التي تبعد 5كم عن مدينة اللاذقية، بهدف دراسة تأثير الرش الورقي ببعض المركبات الدبالية والأحماض الأمينية في نمو وإنتاج هجينين من الخيار(نوفو، دوروك). تم رش أوراق نباتات التجربة بثلاثة مخصبات عضوية (Huzone ،Mol mixs)، وهما مركبان دباليان وAmin vega (حمض أميني).أظهرت النتائج تفوق جميع معاملات الرش الورقي بالمخصبات العضوية بفروق معنوية على معاملة الشاهد في جميع الصفات المدروسة للهجينين المدروسين (طول الساق، عدد الفروع/نبات، عدد الأوراق/نبات، المساحة الورقية، عدد الأزهار على الساق، عدد الثمار على الساق، عدد الأزهار على الفروع، عدد الثمار على الفروع). وقد حققت معاملة الرش بخليط من المركبات الدبالية والأحماض الأمينية زيادة و بفروق معنوية في كل من عدد الأوراق/نبات وعدد الفروع/نبات وطول الساق للنبات وعدد الثمار على الساق في الهجين نوفو. بينما حققت معاملة الرش بالهيوزون زيادة وبفروق معنوية في كل من عدد الفروع/نبات وعدد الأزهار على الفروع وعدد الثمار على الفروع في الهجين دوروك. أما فيما يتعلق بالإنتاج المبكر والإنتاج الكلي، فقد تفوقت معاملة الخليط من المركبات الدبالية والأحماض الأمينية بفروق معنوية على المعاملات الأخرى عند كلا الهجينين نوفو ودوروك وبلغت على التتالي 5)،4,1 كغ/ م2؛ 16، 14,8 كغ/ م2) .The research was conducted in plastic green house for the 2013-2014, in Alqangerh village, about 5 Km from the city of latakia, in order to study the effect of spraying the leaves with some humic compounds and amino acids on growth and production of hybrids of cucumber (Novo,Dorruk). Spraying leaves with three organic fertilizers are (Huzone, Mol mixs), and two boats Dbalin and Amino vega (an amino acid).The results showed that all treatments of leaves spraying with organic fertilizer geve better resultus with significant differences than the control treatment in all the studied traits of both hybrids: (stem length, number of branches/plant, number of leaves/plant, leave area cm2, the number of flowers on the stem, number of fruits on the stem, number of floral branches, number of fruits on the branches).The treatment of spraying achieved with mixture of humic compounds and amino acids increase with significant differences in both the number of leaves/plant, number of branches/plant, the plant's stem length and number of fruit on the stem in the hybrid Novo. while the treatment of spraying achieved of hiozon increase with significant differences the number of branches/plant, the number flowers on the branches and number of fruits on the branches was in the hybrid Dorok. As for the early production and total production, the treatment of spraying with mixture of humic compounds and amino acids with significant differences on other transaction when both hybrids Novo and Dorruk amounted, respectivety (5 ، 4,1 kg/m2 ; 16 ، 14,8 kg/m2 ).